Carcinoembryonic antigen levels correlated with advanced disease in medullary thyroid cancer - Sena Turkdogan; Véronique-Isabelle Forest; Michael P. Hier; Michael Tamilia; Anca Florea; Richard J. Payne (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Medullary thyroid cancer (MTC) cells are capable of secreting various tumor markers including calcitonin and carcinoembyronic antigen (CEA). The purpose of this study is to determine whether abnormal CEA levels may be used as a tumor marker to predict the severity of disease in MTC. Methods A retrospective analysis was completed for 33 patients with MTC who had preoperative serum CEA levels. Univariate and multivariate analyses were used to quantify the relationship between serum CEA levels and tumor stage and prognosis. Results On multivariate analysis, elevated preoperative CEA levels were significantly associated with the size and stage of tumor, distant metastasis, decreased biochemical cure, and mortality. There was a significant association between tumor size greater than 37 mm and elevated CEA levels (> 271 ng/ml). There was also a positive correlation with increased cancer stage (> 377 ng/ml), distant metastasis (> 405 ng/ml), and contralateral compartment location of lymph node metastasis (> 162 ng/ml). When pre-operative CEA levels are > 500 ng/ml, patient mortality was 67%. Conclusion In this study, both pre-operative calcitonin and CEA levels were significantly correlated with the extent of disease in MTC. While calcitonin has a linear relationship with disease progression, abnormal CEA levels were a better indicator of advanced disease. CEA levels > 271 ng/ml are significant for advanced tumor size and staging, metastasis to the central compartment, and decreased chance of biochemical cure. CEA levels greater than 500 ng/ml are associated with significant patient mortality.